The Effect of Product Quality and Service Quality on Customer Satisfaction - Lbn. Raja*, Edward A.; Maharani, Maharani; Raja, John G. Lbn. (Riwayat: Educational Journal of History and Humanities, 2023)
In producing a product, the quality of the product is something that must be done by the company so that consumers will feel satisfied with the product that will be used by the customer. product quality will have an influence on customer satisfaction so that the use of the product will occur at a later time because there is satisfaction. In addition to product quality that will be felt by customers, it is also necessary to provide good service to customers so that customers feel well served by the company or service provider. respondents who serve as the population and research samples are customers Cafe Hans as many as 72 people. The results of the study explain that the effect of product quality on customer satisfaction is T count 91.9% where product quality really has a major influence on customer satisfaction at Hans Caf, the effect of service quality on customer satisfaction is T count 2.7% where product quality only gives a small contribution to customer satisfaction and the influence of product quality and service quality on customer satisfaction is F count of 50% where together product quality and service quality have an influence on customer satisfaction.